2020
DOI: 10.1177/0973258619878354
|View full text |Cite
|
Sign up to set email alerts
|

The Girl Rising ‘We Dream, We Rise’ Social Media Campaign in India: Reach, Engagement and Impact

Abstract: Girl Rising, a global campaign, uses the power of storytelling to build a movement for adolescent girls by inspiring people to change the way girls are valued, and sparking social action. We Dream, We Rise, is a social media campaign that was launched to call attention to age-old gender stereotypes that have gone unquestioned for generations and to inspire adults across the country to ‘dream as big for their girls as they do for their boys’. A descriptive evaluation of the campaign was conducted to measure its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Sentiment analysis is managed by classifying algorithm. Understanding the qualitative dimension of communication on social media is very useful in critical situations, such as a natural disaster to pandemics currently occurring, as social media is a powerful tool for personal communication about their perception of goods and services (Vyas et al, 2020). The development of the internet allows rapid, widespread and easy dissemination of information, which is utilised by the mass media to meet the needs of the public for information.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Sentiment analysis is managed by classifying algorithm. Understanding the qualitative dimension of communication on social media is very useful in critical situations, such as a natural disaster to pandemics currently occurring, as social media is a powerful tool for personal communication about their perception of goods and services (Vyas et al, 2020). The development of the internet allows rapid, widespread and easy dissemination of information, which is utilised by the mass media to meet the needs of the public for information.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Digital media data sources offer several key advantages compared to traditional data sources, including organic insights into audiences' concerns, real-time data, and low-cost collection (Schober et al, 2016;Vyas et al, 2020). Content posted online are spontaneous and curated by the creator (Pasek et al, 2018;Schober et al, 2016), which allow a more organic window into public opinion.…”
Section: Using Social Media To Tailor Science Communication Messagesmentioning
confidence: 99%
“…Given that empowerment is highly contextualised and influenced by society’s norms/culture (Dixit, 2021), another issue worthy of analysis concerns how advocacy organisations in different cultures use social media (Shata & Seelig, in press; Waters & Lo, 2012). In some patriarchal societies, the relationship between men and women negatively impacts women’s empowerment (Vyas et al, 2020). For example, Fatehkia et al (2018) found that Facebook gender gap indicators correlated highly with official statistics on the Internet and mobile phone gender gaps, like in a male-dominated society like Egypt, where there are more male users than female users.…”
Section: Dragonfly Effect Modelmentioning
confidence: 99%